2020
DOI: 10.1103/physrevlett.124.106102
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Chemistry and Faceting at Grain Boundaries in a Model Al Alloy

Abstract: The boundary between two crystal grains can decompose into arrays of facets with distinct crystallographic character. Faceting occurs to minimize the system's free energy, i.e., when the total interfacial energy of all facets is below that of the topologically shortest interface plane. In a model Al-Zn-Mg-Cu alloy, we show that faceting occurs at investigated grain boundaries and that the local chemistry is strongly correlated with the facet character. The self-consistent coevolution of facet structure and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Grain boundary defects, such as ledges, may also act as preferential nucleation sites [46,49]. Zhao et al demonstrated how a grain boundary may decompose into facets with different segregation and precipitation behaviour [50]. The spacing between grain boundary particles may have influence on the presented SCC results, but the statistics from the methods used in this work could not be applied in drawing any conclusions related to this due to the enormous variations between grain boundaries within the same sample.…”
Section: Discussionmentioning
confidence: 92%
“…Grain boundary defects, such as ledges, may also act as preferential nucleation sites [46,49]. Zhao et al demonstrated how a grain boundary may decompose into facets with different segregation and precipitation behaviour [50]. The spacing between grain boundary particles may have influence on the presented SCC results, but the statistics from the methods used in this work could not be applied in drawing any conclusions related to this due to the enormous variations between grain boundaries within the same sample.…”
Section: Discussionmentioning
confidence: 92%
“…We recently reported on the interplay of chemistry and faceting at GBs in the same Al-Zn-Mg-Cu alloy [40] . The GBs show significant different segregation and precipitation behavior along the GB plane.…”
Section: Interplay Of Segregation and Local Structure At Gbsmentioning
confidence: 99%
“…This has resulted in intense efforts to characterise the GBs in 7xxx alloys at the atomic-scale using advanced techniques, such as aberration-corrected scanning transmission electron microscopy (STEM) [4,5,12] and atom probe tomography (APT) [10,11,13,14]. In recent work, on which we focus herein, APT revealed significant solute segregation to GBs, in a model as-quenched Al-Zn-Mg-Cu alloy [11,15], and a significant acceleration of the sequence of precipitation compared to that found in the bulk of the grains. Grain-size effects on segregation have also been investigated, with higher Zn segregation being observed in a coarse-grained alloy compared to in an ultrafine-grained alloy, while similar Mg and Cu segregation levels were observed [11,13,14].…”
Section: Introductionmentioning
confidence: 99%